Hard ticks infesting domestic ruminants, species composition and infection with Crimean-Congo hemorrhagic fever virus in a highland province, SW Iran - Zahra Hosseini; Mostafa Salehi Vaziri; Sara Ahmadnia; Mohammad Reza Fakoorziba; Tahmineh Jalali; Zakkyeh Telmadarraiy; Mohammad Djaefar Moemenbellah-Fard (Shiraz University of Medical Sciences, 2019)
Background: Crimean-Congo hemorrhagic fever (CCHF) is a neglected tick-borne viral zoonotic disease. The aim was to detect CCHF virus (CCHFV) among wild ticks from Artiodactyla, Bos taurus, Ovis aries, and Capra hircus, in a previously declared CCHFV-free province of Kohgiluyeh Boyer-Ahmad, southwest Iran. Methods: From April to November 2015, hard ticks were collected in a cross-sectional study and checked by microscope for species identity from ungulates in 51 study villages. About 55% of the ticks were then subjected to reverse-transcription polymerase chain reaction (RT-PCR) to detect CCHFV genome. Results: Overall, 859 hard ticks were captured, from which 8 different species in two genera were identified. The genus Rhipicephalus was distributed in half (#26) of the study villages. It was the most frequent (≈60%) tick genus. Hyalomma anatolicum, H. asiaticum, H. excavatum, H. marginatum, H. scupense, Rhipicephalus sanguineus, R. turanicus, and R. bursa were identified on the ruminants. From 469 adult ticks subjected to RT-PCR, one (0.2%) tick, R. bursa, was positive with CCHFV genome. It was from a cold hardy highland village in Dena County. It had CCHFV RNA for the first time from this region. Conclusion: The detection of CCHF viral RNA in one hard tick species, R. bursa, was confirmed in the southwest of Iran, thus partially indicating CCHFV presence of ticks in this region.